Makna Pandangan Eskatologi “Premelianisme” Bagi Orang Percaya Masa Kini - Thomas Bedjo Oetomo (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2022)
The Bible is a source of accurate doctrine. The application of hermeneutic principles by theologians produces views. The dissimilarity in the use of hermeneutic principles results in the alteration of the doctrines that are believed. There is dissimilarity in the doctrine of eschatology among theologians, due to differences in hermeneutic principles in interpreting biblical texts. Discrepancy of theological understanding will also be followed by the diversity of church denominations. Dissimilarity of church doctrine is a necessity and until the second coming of Christ, it is impossible to make similarity. This fact should not keep the church busy seeking to justify its own doctrine and demean the doctrines of other churches. As a result, the church can forget its main mandate, which is to carry out the Great Commission of Christ. ABSTRAK BAHASA INDONESIA Alkitab adalah sumber doktrin yang akurat. Penerapan prinsip hermeneutik oleh para teolog menghasilkan pandangan-pandangan. Disimilaritas penggunaan prinsip hermeneutik mengakibatkan terjadinya alterasi doktrin yang diimani. Adanya disimilaritas doktrin eskatologi di kalangan para teolog, dikarenakan perbedaan prinsip hermeneutik dalam menginterpretasikan teks-teks Alkitab. Diskrepansi paham teologi akan diikuti pula keragaman denominasi gereja. Disimilaritas doktrin gereja adalah sebuah keniscayaan dan sampai kedatangan Kristus kedua kalipun, mustahil untuk dijadikan similaritas. Fakta ini sebaiknya tidak membuat gereja sibuk mencari pembenaran doktrinnya sendiri-sendiri dan merendahkan doktrin gereja-gereja lain. Akibatnya gereja bisa melupakan mandat utamanya, yaitu menyelenggarakan Amanat Agung Kristus.